Phenomenological Study on The Contribution of Food Safety Perception in Consumer Purchasing Interest - Wijaya, Hartadi (Green Publisher Indonesia, 2025)
Food safety is a critical concern for modern consumers, influencing purchasing decisions globally. This study examines how food safety perceptions shape consumer buying interest in Indonesia, addressing gaps in localized, qualitative insights. Using a phenomenological approach, in-depth interviews were conducted with eight respondents from diverse demographics (students, employees, managers, and business owners) to explore their priorities (safety, price, taste, nutrition) and safety-assessment behaviors (e.g., checking expiry dates, seller cleanliness). Findings reveal that personal health experiences (e.g., food poisoning, chronic conditions) and demographic factors (age, income) significantly influence safety prioritization, with older or health-affected consumers valuing safety most. Key determinants of trust include seller reputation, product physical condition, and hygiene standards. The study highlights practical implications for businesses: enhancing transparency, innovating health-centric products, and maintaining rigorous hygiene to align with consumer expectations. By contextualizing global frameworks within Indonesia’s market, this research offers novel insights for policymakers and marketers to tailor strategies that address localized safety concerns and foster consumer trust.